Approaches on Modelling Genes Interactions: A Review - Hammadi, Dhafar Sami; Mahmood, Basim; Dabdawb, Marwah M. A. (Technium BioChemMed, 2021)
The human genome is a set of humans’ nucleic acid sequences that are encoded as DNA in the human chromosome pairs. These are usually treated separately as the nuclear genome and the mitochondrial genome. Studying and understanding genetic systems has a great impact on health. Therefore, in the last few decades, the world has witnessed a great revolution in genetic engineering that aims to identify new phenomena and support mitigating the effect of diseases or even find ultimate solutions. The first step in studying genetics data is modelling this data and use some analysis approaches. The main problem of researchers is finding appropriate approaches for modelling their genetics data. This work comes to review the literature and present a variety of approaches used by researchers in modelling genetics data and genes interactions. This review tries to make it easy for researchers when adopting particular modelling approaches by presenting the state-of-the-art in terms of the dataset used, strengths, and limitations.